Pleurotus ostreatus is a potential biological control agent of root-knot nematodes in eggplant (Solanum melongena) - Nyangwire, Betty; Ocimati, Walter; Tazuba, Anthony Fredrick; Blomme, Guy; Alumai, Alfred; Onyilo, Francis (Frontiers in Agronomy, 2024)
IntroductionThe management of root-knot nematodes has predominantly been based on use of chemicals, which are detrimental to the environment and human health. Biological control provides alternative management. This study evaluated the potential of using Pleurotus ostreatus, an edible mushroom species to control Meloidogyne spp. in eggplants.MethodsIn vitro, the mortality of juveniles (J2) of Meloidogyne spp. were assessed i) P. ostreatus - water suspension with actively growing mycelia, and ii) different dilutions of P. ostreatus PDB broth culture filtrates. In the screen house nematicidal potential of P. ostreatus was tested on eggplants using artificially inoculated soils in a screen house. To attain this, juveniles (J2) of Meloidogyne spp. were inoculated at the base of plants in pots containing P. ostreatus colonized millet grains mixed in 3 kg of soil. The galling index (GI) (scale of 0 to 5), root growth and nematode populations in the different treatments were assessed.Results and discussionMortality of nematodes in the P. ostreatus - water suspension significantly increased with time, reaching over 88% at 48 h and 95% at 72 h. Mortality in undiluted filtrate was consistently significantly higher than the diluted filtrates and control without P. ostreatus. Mortality in the undiluted filtrate increased to 95% at 48 h. When 50 g of P. ostreatus-millet culture was mixed with 3 kg autoclaved pot soil, a GI of 0.95 was observed, dropping to 0.70 when the inoculum was doubled to 100 g. For the treatment without P. ostreatus, a high GI of 2.4 was scored. A significant difference in eggplant root growth and nematode population at (p = 0.02) was found across the treatments. The findings from this study for both in-vitro and pot assay suggest that P. ostreatus and its substrate are potential biological control agents for plant parasitic nematodes in eggplants.